TI_GERICHTE 52.2013.19 vom 30. Juni 2014 , Licenza edilizia per un vigneto. Agricoltura esercitata a titolo di hobby - TI Tribunale d'appello (2014)
Licenza edilizia per un vigneto. Agricoltura esercitata a titolo di hobby